Back Cover: Potent and Selective Inhibitors of Trypanosoma cruzi Triosephosphate Isomerase with Concomitant Inhibition of Cruzipain: Inhibition of Parasite Growth through Multitarget Activity (ChemMedChem 12/2016). (21st June 2016) - Aguilera, Elena; Varela, Javier; Birriel, Estefanía; Serna, Elva; Torres, Susana; Yaluff, Gloria; de Bilbao, Ninfa Vera; Aguirre‐López, Beatriz; Cabrera, Nallely; Díaz Mazariegos, Selma; de Gómez‐Puyou, Marieta Tuena; Gómez‐Puyou, Armando; et al.
Abstract : The back cover picture shows the development of multitarget agents that act against triosephosphate isomerase (TIM) and cruzipain, two key enzymes in Trypanosoma cruzi, the causative agent of Chagas disease. The compounds exhibited a nanomolar range of inhibition in TIM and a protective profile in vivo. These molecules were synthesized using green chemistry principles and at low cost, which are very important issues regarding the treatment of neglected diseases. Additionally, one of the reactants was derived from cereal husk, a waste product of the food industry. The inhibition of two metabolic pathways by the same compound has a great advantage in avoiding resistance to the developed drug. More information can be found in the Full Paper by Guzmán Alvarez et al. onpage 1328 in Issue 12, 2016 (DOI:10.1002/cmdc.201500385 ).